Foye’s principles of medicinal chemistry (Lippincott Williams & Wilkins, 2008)
The new edition has been fully revised and updated to meet the changing curricula of medicinal chemistry courses. Emphasis is on patient-focused pharmaceutical care and on the pharmacist as a therapeutic consultant, rather than a chemist. A new disease state management section explains appropriate therapeutic options for asthma, chronic obstructive pulmonary disease, and men's and women's health problems. Also new to this edition: Clinical Significance boxes, Drug Lists at the beginning of appropriate chapters, and an eight-page color insert with detailed illustrations of drug structures. Case studies from previous editions and answers to this edition's case studies are available online at thePoint